Mice Lacking Ras-GRF1 Show Contextual Fear Conditioning but not Spatial Memory Impairments: Convergent Evidence from Two Independently Generated Mouse Mutant Lines - d'Isa, Raffaele; Clapcote, Steven J.; Voikar, Vootele; Wolfer, David P.; Giese, Peter; Brambilla, Riccardo; Fasano, Stefania (Frontiers in Behavioral Neuroscience, 2011)
Ras-GRF1 is a neuronal specific guanine exchange factor that, once activated by both ionotropic and metabotropic neurotransmitter receptors, can stimulate Ras proteins, leading to long-term phosphorylation of downstream signaling. The two available reports on the behavior of two independently generated Ras-GRF1 deficient mouse lines provide contrasting evidence on the role of Ras-GRF1 in spatial memory and contextual fear conditioning. These discrepancies may be due to the distinct alterations introduced in the mouse genome by gene targeting in the two lines that could differentially affect expression of nearby genes located in the imprinted region containing the Ras-grf1 locus. In order to determine the real contribution of Ras-GRF1 to spatial memory we compared in Morris Water Maze learning the Brambilla’s mice with a third mouse line (GENA53) in which a nonsense mutation was introduced in the Ras-GRF1 coding region without additional changes in the genome and we found that memory in this task is normal. Also, we measured both contextual and cued fear conditioning, which were previously reported to be affected in the Brambilla’s mice, and we confirmed that contextual learning but not cued conditioning is impaired in both mouse lines. In addition, we also tested both lines for the first time in conditioned place aversion in the Intellicage, an ecological and remotely controlled behavioral test, and we observed normal learning. Finally, based on previous reports of other mutant lines suggesting that Ras-GRF1 may control body weight, we also measured this non-cognitive phenotype and we confirmed that both Ras-GRF1 deficient mutants are smaller than their control littermates. In conclusion, we demonstrate that Ras-GRF1 has no unique role in spatial memory while its function in contextual fear conditioning is likely to be due not only to its involvement in amygdalar functions but possibly to some distinct hippocampal connections specific to contextual learning.